PERAN ORGANISASI INTERNASIONAL PADA PELANGGARAN HUKUM INTERNASIONAL YANG DILAKUKAN OLEH ZIONIS ISRAEL TERHADAP KONFLIK DENGAN PALESTINA - Jumhana, Enjum (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
An international organization is an organizational forum formed and consisting of more than one country, created on the basis of equality, whether the aim is to produce or create peace in the world and in the international relations system. Israel's aggression against Palestine received a strong reaction from international countries because of the large number of victims caused by this action, most of whom were civilians. According to humanitarian law and international law, Israel's aggression against Palestine has violated the principles of humanitarian law, namely: the principle of humanity, the principle of limitation and the principle of distinction. Israel has committed war crimes so the international community asks how can Israel commit war crimes and be prosecuted? There are three mechanisms for enforcing humanitarian law. Firstly, the parties to the Geneva Conventions contract to enact whatever laws are necessary to provide effective criminal sanctions for persons who commit or order to commit any of the serious offences, secondly by ad hoc tribunals and thirdly by the Criminal Court Internationally, but it is quite difficult to prosecute Israel because Israel has not ratified the 1998 Rome Statute. Here the author will provide an explanation of 4 main points, namely: 1. What is the actual legal position of the parties to the Palestinian and Israeli conflict, 2. Violations of international law which has been done by Israel, 3. The role of international organizations in implementing international law in this case through the UN, 4. What can the international community, in this case the State of Indonesia, do to make a real contribution to resolving the Palestinian and Israeli conflict